INTEGRASI BLOCKCHAIN DAN ARTIFICIAL INTELLIGENCE PADA KURIKULUM AKUNTANSI: SYSTEMATIC LITERATURE REVIEW - Adrian, Fariz Hudi; Dewayanto, Totok (Diponegoro Journal of Accounting, 2024)
This study aims to conduct research on the integration of blockchain and artificial intelligence in the accounting curriculum in accounting education institutions. This research uses the systematic literature review (SLR) method in analyzing 20 articles published on the Scopus database with a range of years published 2021-2024. The literature search design guidelines use the PICO framework and articles are screened using the Preferred Reporting Items for Systematic Reviews and Meta Analyses (PRISMA) protocol. The results of the analysis in this study state that the current accounting curriculum needs to be updated to meet the needs of a rapidly growing industry with modern technology. The integration of fintech, blockchain, and artificial intelligence is essential to ensure graduates have skills that are relevant to the demands of the job market and reduce the gap between employer expectations and graduate skills. The integration of these technologies in the accounting curriculum will increase the relevance and modernization of learning materials, improve the quality of education, and encourage innovation in teaching. However, there are challenges to be faced, such as a crowded curriculum, lack of resources and expertise of educators, and privacy and security concerns. However, with global market pressures, adaptive organizational cultures, technological benefits, collaborative support, and adequate infrastructure, this integration can be managed wisely to prepare students for digital transformation and open up wider career opportunities.